Does household tax burden have an impact on individuals' savings in banks? The case of Ukraine - Gennadiy Sudak; Savchenko Yuliia (Central European Economic Journal (CEEJ), 2021)
This paper aims to assess the impact of the effective and nominal household tax burden on household deposits in Ukrainian banks. We used the effective tax burden, which includes personal income taxes and value-added tax (VAT) paid. We considered changes in Ukrainian tax law from 2003 to 2016, which included a change from progressive income taxation to proportional income taxation, a decrease in tax rates in 2003, and an increase in tax rates in 2014-2016. The data sample consists of publicly available data on Ukrainian households' income, savings, and taxes paid in 1996-2019. The analysis was performed using panel regression and the difference-in-difference (DID) method. The tax burden impact on bank deposits is significant and is caused partly by the shadow economy. The results of the study are relevant for Ukraine and countries with similar economies. The methodological approaches developed in the paper can be used for similar studies in other developing countries.
Keywords: H21; H24; H31; E27; 330; direct taxes; indirect taxes; personal income tax; government revenue; taxable income; effective tax burden; consumption; income structure; spending structure; savings; bank deposits; Ukraine